Recursos de linguagem na animação: a enunciação cinematográfica construída a partir das transformações da figuratividade quadro a quadro - Menezes, Maria Christina (2005)
Definition of issue and objectives: This work aims to identify and review some of the resources of animation movies, determined by its specific production processes with several subjects, frame by frame, that recognises it as a special form of cinematographic language. Which are the specificities of cinematographic enunciation that are intrinsic to the frame-by-frame production mode? The objective is to identify the peculiar resources of animation language, which, historically, has evolved through several variants of this productive process. Corpus: An analysis of twelve animation films produced from the 20th century s first decades to the 90 s will be carried out. These are illustrative of the transformations of figurativeness through the frame-by-frame production process, which create the following resources in the construction of filmic discourse: (1) metamorphosis, (2) overlapping of image layers; (3) disruption of movement illusion; (4) visual puns. Overview of theoretical reference: Initially, I will mainly consider the concepts worked by the following authors: 1. about the structural attributes of cinematographic language (enunciation in the cinema, editing, connections and transitions): Christian Metz, Francis Vanoye, Marcel Martin, Arlindo Machado, Marshall McLuhan, Sergei Eisentein e André Parente; 2. for the approach of grammar and the elements that make up the two-dimensional plastic text (the dot, the line, the colour, the shape; concepts of figure and background, of disfigurement, of contrasted or levelled composition, etc): Rudolf Arnheim, Jacques Aumont, Donis A. Dondis, Jean Marie Floch e Aljirdas Greimas; 3. about animation cinema (its techniques, the evolution of language on account of its history and the creation process of certain animators): Alberto Lucena Jr., Maureen Furniss, Robert Russett & Cecile Starr. Pertinence to the field of Communication: The research essentially relates to the domain of the interface of texts with its production mode. It studies animation language as a result of the animation cinema media. It is also possible to identify the domain of the interface of texts with the media marks, considering that, if animation language has hybrid elements of the cinematographic language and the visual language of plastic arts, it is necessary to analyse the corpus taking into account what the messages carry from each one of these languages, and in this way penetrate its own qualities